Comparison between outcomes of IgA nephropathy with nephrotic-range proteinuria and nephrotic syndrome: do podocytes play a role?. Issue 1 (31st December 2022) - Chen, Yizhen; Yang, Aicheng; Hou, Yuansheng; Liu, Longhui; Lin, Jiehua; Huang, Xiaodan; Li, Jundu; Liu, Xusheng; Lu, Fuhua; Lin, Qizhan; Yang, Haifeng; Yue, Shuling; et al.
Abstract: Background: Nephrotic syndrome (NS) and nephrotic-range proteinuria (NRP) are uncommon in IgA nephropathy (IgAN), and their clinicopathology and prognosis have not been discussed. Podocytes may play an important role in both clinical phenotypes. Methods: We investigated 119 biopsy-proven IgAN patients with proteinuria over 2 g/d. The patients were divided into three groups according to proteinuria level: the overt proteinuria (OP) group, NS group, and NRP group. In addition, according to the severity of foot process effacement (FPE), the patients were divided into three groups: the segmental FPE (SFPE) group, moderate FPE (MFPE) group, and diffuse FPE (DFPE) group. The outcome was survival from a combined event defined by a doubling of the baseline serum creatinine and a 50% reduction in eGFR or ESRD. Results: Compared with the NRP group, patients in the NS group had more severe microscopic hematuria, presented with more severe endocapillary hypercellularity and had a higher percentage of DFPE. The Kaplan–Meier curve showed that MFPE patients had a better outcome in the NRP group <50% of tubular atrophy/interstitial fibrosis. In the multivariate model, the NRP group (HR = 17.098, 95% CI = 3.835–76.224) was associated with an increased risk of the combined event, while MFPE (HR = 0.260, 95% CI = 0.078–0.864; p  = 0.028) was associated with a reduced risk of the combined event. After the addition of renin-angiotensin system inhibitors (RASi), the incidence of the combined event in the MFPE group (HR = 0.179, 95% CI = 0.047–0.689; p  = 0.012) was further reduced. Conclusions: NS presented more active lesions and more severe FPE in IgAN. NRP was an independent risk factor for progression to the renal endpoint, while MFPE indicated a better prognosis in NRP without obvious chronic renal lesions, which may benefit from RASi.